The Effect of Mindfulness Program on Children's Attention and Depressive Tendency - Feng-Ying Huang; Ruey-Woei Deng (National Taipei University of Education, 2017)
Previous research measuring the effectiveness of Mindfulness Training for children has reported that such training can produce positive effects on their ability to pay attention and psychological well-being. This current research aims to investigate the effects of mindfulness training programs on Taiwan elementary school third-grade students regarding their attention ability, depressive symptoms, and interpersonal relationships with others. This study consisted of 34 third grade students. The participants were recruited from an elementary school in Taipei during a parent-teacher conference, and by disseminating leaflets, all of whom were randomly assigned to the experimental group or the control group. Students in the experimental group (17 of 34) attended the mindfulness teaching program for ten weeks, with each class lasting 40 minutes. The rest of the students made up the control group and attended a regular reading class for an equivalent amount of time. Both questionnaires and semi-structured interviews with children were used to test the effects of mindfulness intervention. The results from the mixed design of two-way ANOVA analyses revealed significant improvements in attention and a decrease in depression symptoms. Furthermore, children from the mindfulness group also reported developing better strategies for managing their emotions and stress, as well as better interpersonal relationships with their peers. Therefore, the Mindfulness Training Program seems to be a promising intervention program that increases children's attention and emotion regulation.